Bright young women eaudiobook A novel. - Knoll, Jessica (Simon & Schuster Audio, 2023)
Don't miss this "breakneck thriller" that examines "our culture's obsession with serial killers and true crime" ( Harper's Bazaar ) as it follows two women on the pursuit of justice against all odds. "A fascinating look at true crime and tabloid culture that's as thoughtful as it is gripping" ( People ). A New York Times Notable Book of 2023 New York Times Editors' Choice Instant New York Times Bestseller A Goodreads Choice Award Finalist Named a Best Book of the Year by NPR, The Washington Post , Harper's Bazaar , Kirkus Reviews , CrimeReads , Booklist , and more! An Edgar Award Finalist for Best Novel Masterfully blending elements of psychological suspense and true crime, Jessica Knoll—bestselling author of Luckiest Girl Alive and the writer behind the Netflix adaptation starring Mila Kunis—delivers an "unflinching and evocative" (Laura Dave, New York Times bestselling author) thriller in Bright Young Women. The book opens on a Saturday night in 1978, hours before a soon-to-be-infamous murderer descends upon a Florida sorority house with deadly results. The lives of those who survive, including a sorority president and key witness, Pamela Schumacher, are forever changed. Across the country, Tina Cannon is convinced her missing friend was targeted by the man the papers refer to as the All-American Sex Killer—and that he's struck again. Determined to find justice, the two join forces as their search for answers leads to a final, shocking confrontation. With award-winning storytelling, " Bright Young Women doesn't put its focus on the murderer. It's more interested in his victims—and the survivors who are on a mission to catch him before he kills again" ( Time ). Blisteringly paced, it is a "compelling, almost hypnotic read and I loved it with a passion" (Lisa Jewell, New York Times bestselling author).